Chronic Embryo‐Larval Exposure of Fathead Minnows to the Pharmaceutical Drug Metformin: Survival, Growth, and Microbiome Responses. (2nd June 2021) - Parrott, Joanne L.; Restivo, Victoria E.; Kidd, Karen A.; Zhu, Juliet; Shires, Kallie; Clarence, Stacey; Khan, Hufsa; Sullivan, Cheryl; Pacepavicius, Grazina; Alaee, Mehran
Abstract: Metformin is a glucose‐lowering drug commonly found in municipal wastewater effluents (MWWEs). The present study investigated the chronic effects of metformin in early‐life stages of the fathead minnow ( Pimephales promelas ). Endpoints assessed were growth, survival, and deformities. The larval gut microbiome was also examined using 16 S ribosomal RNA gene amplicon sequencing to determine microbial community composition and alpha and beta diversity. Eggs and larvae were exposed to metformin measured concentrations (mean [standard deviation]) of 0.020 (0.017) μg/L (for controls) and 3.44 (0.23), 33.6 (1.6), and 269 (11) μg/L in a daily static‐renewal setup, with 20 embryos per beaker. The low and middle metformin exposure concentrations represent river and MWWE concentrations of metformin. To detect small changes in growth, we used 18 replicate beakers for controls and 9 replicates for each metformin treatment. Over the 21‐d exposure (5 d as embryos and 16 d posthatch [dph]), metformin did not affect survival or growth of larval fish. Hatch success, time to hatch, deformities in hatched fry, and survival were similar across all treatments. Growth (wet wt, length, and condition factor) assessed at 9 and 16 dph was also unaffected by metformin. Assessment of the microbiome showed that the larvae microbiome was dominant in Proteobacteria and Firmicutes, with small increases in Proteobacteria and decreases in Firmicutes with increasing exposure to metformin. No treatment effects were found for microbiome diversity measures. Control fish euthanized with the anesthetic tricaine methane sulfonate had decreased alpha diversity compared to those sampled by spinal severance. This experiment demonstrates that metformin at environmentally relevant concentrations (3.44 and 33.6 μg/L) and at 10 times MWWE concentrations (269 µg/L) does not adversely affect larval growth or gut microbiome in this ubiquitous freshwater fish species. Environ Toxicol Chem 2022;41:635–647. © 2021 Her Majesty the Queen in Right of Canada. Environmental Toxicology and Chemistry published by Wiley Periodicals LLC on behalf of SETAC. Reproduced with the permission of the Minister of Environment and Climate Change Canada. Abstract : Fathead minnows exposed to environmentally‐relevant concentrations of the glucose‐lowering drug metformin had no changes in hatching, deformities, survival, or growth. The larval gut microbiome was also not affected by metformin exposure.